1963
DOI: 10.1530/jrf.0.0050059
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation Rates and Litter Sizes in Sexually Receptive and Nonreceptive Artificially Inseminated Rabbits Given Varying Dosages of Luteinizing Hormone

Abstract: At any one time a large proportion of individually caged, sexually mature female rabbits failed to copulate. Intravenous adminis¬ tration of purified pituitary luteinizing hormone (plh) (Armour) produced ovulations in sexually receptive and nonreceptive does alike. Does with histories of infertility ovulated after the injection of plh. The routine administration of 2-5 mg of plh to fifty-seven virgin and multiparous Dutch-Belted does averaging 2 to 3 kg, followed by artificial insemination, resulted in 91% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1965
1965
2004
2004

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The difference may be due to the fact that the cumulative control data were obtained during the various seasons occurring over a period of 1^years. A single intravenous injection of lh into the mature Dutch-Belted doe was previously reported to result in ovulation in virtually every animal (Foote, Hafs, Staples, Grégoire & Bratton, 1963). After similar lh administration to thirty-two smaller Dutch-Belted does in this study, only eleven had cl when laparotomized 18 days later.…”
supporting
confidence: 52%
“…The difference may be due to the fact that the cumulative control data were obtained during the various seasons occurring over a period of 1^years. A single intravenous injection of lh into the mature Dutch-Belted doe was previously reported to result in ovulation in virtually every animal (Foote, Hafs, Staples, Grégoire & Bratton, 1963). After similar lh administration to thirty-two smaller Dutch-Belted does in this study, only eleven had cl when laparotomized 18 days later.…”
supporting
confidence: 52%
“…Templeton (1940) found that force mating of non-receptive females caused only two of five to ovulate, and only five of twenty does maintained a pregnancy to term if force bred to an intact male 17 or more days after a sterile mating. A low incidence of ovulation after force mating was also reported by Foote, Hafs, Staples, Grégoire & Bratton (1963). Mere rubbing of the vulva was reported to cause ovulation in two of four attempts ; how¬ ever, this finding was not confirmed by Shibata (1931).…”
Section: Introductionmentioning
confidence: 64%
“…The ovulation inducing method most frequently used is an intramuscular injection of GnRH or its synthetic analogues [4][5][6]. Alternatively, LH or hCG can be used to induce ovulation in rabbit does [7], however, the repeated injection of these hormones can result in failure of the does to ovulate due to antibody formation [8]. Vasectomised males have been used to induce ovulation in does submitted to AI [9,10], but the method is time-consuming and some females refuse to mate, but ovulate when given LH or GnRH.…”
Section: Introductionmentioning
confidence: 99%